Poetic Generations Variation of Term and Sensitivity of Concept (Journal of Hama University, 2019)
This research follows the phenomenon of the poetic generations, through the opinions of some critics and scholars and practitioners on this phenomenon, whose opinions varied and varied between the answerable according to specific criteria and considerations pointed out by the research, and skeptical of these standards, rejecting the whole and the issue of "generating" absolute. The research presented the most prominent of these views according to a vision that claims that it does not reject an opinion and does not adopt another as much as it is used and adopted, which differed in its definition of the term "generation". Under the guidance of their own understanding of the relatively from, according to cultural and cognitive contexts, On the sensitivity of the concept of "Generation", which marked a milestone on the map, which linked the literary output with time, and made the process of "Generating" problematic.The research also showed the concept of generation in the fields of lexicography and literature, and presented its vision of "Generating", and its perception of how generations form, and pointed to the most important determinants that can determine the features of the generation, in addition to the factors that may affect the movement and direction. It pointed to the existence of points of intersection between the processes of "Generating" and "Chronolization", despite the mismatch of their concepts, and the different approach applied and procedural mechanism in each. It also referred to the role of "Generating" and its importance for the scholars of literature and critics and the members of society that embraces the generation. All  are within the framework of the critical views that stopped the research.